AGRANULOSIT OF BALI CATTLE ON VARIOUS AGE IN NUSA PENIDA - Andung, Franki Remi; Suwiti, Ni Ketut; Kendran, Anak Agung Sagung (Buletin Veteriner Udayana, 2018)
The study aims to determine the percentage ratio of agranulocytes at several ages of of Bali cattle calve. This study used female Bali cattle which reared in the area of Nusa Penida, with three different age ranges namely the calves, the virgins, and the adults. The blood sampling was performed through the jugular vein using venoject and it was instantly made a blood smear on the research sites. The preparation was observed and calculated under a microscope with a magnification of 1000 times using cross sectional method, the number of lymphocytes and monocytes were observed and calculated per 100 leukocytes. The data obtained were then analyzed by using analysis of variance test one-way Anova. The results indicated a difference in the percentage of lymphocytes was very significant on the calves the virgins, and the adults’s age level. While there were no significant differences on monocytes. The results showed that the percentage of lymphocytes in adults age is higher than the age of the calves and the virgins. While the percentage of monocytes has the same value at age.